Factors associated with Exacerbation of Myasthenia Gravis in a Group of Iraqi Patients - Al Dulaimy, Ahmed Abdalrazak; Al-Mashtah, Sarmad Abdul Rasool; Ahmed, Muna Haider (AL-Kindy College Medical Journal, 2023)
Background: Myasthenia gravis is an autoimmune disease of the neuromuscular junction that results in fluctuating muscle weakness as well as significant fatigue. Disease exacerbation is a critical condition, and the predisposing factors for it need to be identified to improve preventive measures. Objectives: Our study aims to determine the predisposing factors for myasthenia gravis exacerbations in a group of Iraqi patients. Subjects and Methods: A total number of 30 myasthenia gravis patients were admitted to the hospital with an exacerbation of their symptoms, determined as the development of functional disability, dysphagia, or respiratory failure within one month prior to admission. Each patient was assessed by history taking, clinical examination, and investigations to determine the possible exacerbating factor. Results: There were (56.7%) of patients with infection. Non-compliance to treatment was found in (26.7%) of patients, and medication induced exacerbation was found in (16.7%) of the patients. Conclusion: Infection is the most common predisposing factor for disease exacerbation and is associated with an unfavorable outcome.